Sampling mass mortality events to enable diagnoses: A protocol using freshwater mussels - Daniel A. Cossey; Michelle M. Dennis; Jordan Richard; Camilla Della Torre; Andrew McElwain; Diane L. Waller; Susan Knowles; Joshua I. Brian; Eric Leis; Erika A. V. Burioli; David C. Aldridge (Methods in Ecology and Evolution)
Abstract Many taxa around the globe are threatened by often unexplained mass mortality events (MMEs), which can decimate populations and compromise key ecosystem functions. One example of a highly threatened taxon facing frequent MMEs is freshwater mussels (Unionida). There has been a recent increase in interest in understanding the causes of freshwater mussel MMEs, but standardised methodologies for how best to respond to them to facilitate diagnoses are unavailable. When an MME is observed, swift and appropriate sample collection is imperative owing to the transient nature of these phenomena. Here we provide structured guidance that will facilitate rapid and appropriate sampling of MMEs, using freshwater mussels as an example. We set out standardised procedures for sample collection, preparation and preservation. The procedures we outline will improve our capacity for diagnostic investigations of MMEs and other mortality events, not only in freshwater mussels but also across many other taxa. This, in turn, can inform appropriate management responses.